Therapeutic targeting of two-pore-domain potassium (K2P) channels in the cardiovascular system - Wiedmann, Felix Tobias; Schmidt, Constanze; Lugenbiel, Patrick; Staudacher, Ingo; Rahm, Ann-Kathrin; Seyler, Claudia; Schweizer, Patrick Alexander; Katus, Hugo; Thomas, Dierk (Clinical science, 2016)
The improvement of treatment strategies in cardiovascular medicine is an ongoing process that requires constant optimization. The ability of a therapeutic intervention to prevent cardiovascular pathology largely depends on its capacity to suppress the underlying mechanisms. Attenuation or reversal of disease-specific pathways has emerged as a promising paradigm, providing a mechanistic rationale for patient-tailored therapy. Two-pore-domain K+ (K2P) channels conduct outward K+ currents that stabilize the resting membrane potential and facilitate action potential repolarization. K2P expression in the cardiovascular system and polymodal K2P current regulation suggest functional significance and potential therapeutic roles of the channels. Recent work has focused primarily on K2P1.1 [tandem of pore domains in a weak inwardly rectifying K+ channel (TWIK)-1], K2P2.1 [TWIK-related K+ channel (TREK)-1], and K2P3.1 [TWIK-related acid-sensitive K+ channel (TASK)-1] channels and their role in heart and vessels. K2P currents have been implicated in atrial and ventricular arrhythmogenesis and in setting the vascular tone. Furthermore, the association of genetic alterations in K2P3.1 channels with atrial fibrillation, cardiac conduction disorders and pulmonary arterial hypertension demonstrates the relevance of the channels in cardiovascular disease. The function, regulation and clinical significance of cardiovascular K2P channels are summarized in the present review, and therapeutic options are emphasized.